Farmers’ Varietal Perception towards Improved Bread Wheat Technologies in Ethiopia: an Implication for Bread Wheat Technology Development - Negussie Muluneh Siyum; Almaz Giziew; Atrsaw Anteneh; Jhon Hardy Purba; Habtamu Mossie; Emam Adem (Agro Bali : Agricultural Journal, 2023)
This study was proposed to analyze farmers’ varietal perception of bread wheat. From Meket district, four kebeles were randomly selected to achieve the above objective. The study uses cross-sectional data collected from randomly selected 214 farming households through an interview schedule. Fourteen Likert items were included in two categories as advantages and disadvantages of the technology.  Five-point Likert scale was used to analyze varietal perceptions. One-way ANOVA was employed for testing the overall mean differences among bread wheat technology adoption categories. In addition, the Relative Importance Index (RII) was used to analyze item relative importance. Farmers supported improved bread wheat varieties for specific attributes such as, high marketability, early maturity, better grain yield, grain color, food quality, and storability were found to be taking the average score of 4.43, 4.43, 4.33, 4.01, 3.85, 3.45, and 3.26, respectively. Whereas, improved bread wheat varieties were perceived to be unsuitable for shattering problems, straw quality, and low yield performances in poor soil types. Therefore, breeding objectives should be oriented towards improving bread wheat variety traits related to shattering and straw quality. Limitation of labor is one of the major reasons for the low adoption rate of row planting. Hence, machinery should be carried out to promote row planting of bread wheat. Moreover, the study indicates the need to entertain farmers’ perception of bread wheat technologies for creating wider adoption.